A Manager's Toolbox for Consumer-Centric Food Packaging - Eva Marckhgott; Bernadette Kamleitner (Marketing Review St.Gallen, 2021)
At the point of sale, packaging is often one of the few means for companies to answer implicit questions that (potential) consumers might have before buying food products. This paper provides a novel toolbox that supports companies in designing consumer-centric packaging that assists consumers in their purchase decisions.
Keywords: 650